Effects of Selective Extraction of Histones on Template Activities of Chromatin by Use of Exogenous DNA and RNA Polymerases - Mirsky, Alfred E. (1973)
Exogenous DNA and RNA polymerases were used to measure the template activity of DNA in chromatin in isolated thymus nuclei from which lysinerich or arginine-rich histones were selectively extracted. Measurements were on nuclei containing 20-1200 μg of DNA per ml, the distinctions becoming clear at the higher concentrations. Experiments with RNA polymerase showed only moderate increases in template activity upon extraction of histone, although the removal of lysinerich histone had a greater effect than that of arginine-rich histone. DNA polymerase action on nuclei minus lysinerich histone achieved high results, exceeding even those on DNA itself.